Diversity of Seagrass Species in The Conservation Area of The Sawu Sea Marine National Park (TNP) - Lambok Laurence Silaban; Fakhrurrozi Fakhrurrozi; Juraij Juraij; M Rizki Fauzi; Chandrika Eka Larasati; Ibadur Rahman (Jurnal Biologi Tropis, 2023)
The Sawu Sea is an important habitat for dolphins, dugongs, manta rays and turtles. Sabu Island is one of the locations included in the Sawu Marine National Park area with considerable seagrass potential. The purpose of this study was to determine the health condition and community structure of seagrass on Sabu Island. This study used line transect, square transect, and random transect methods. The results of observations found 8 species, the most common types of seagrass were Thalassia hemprichii, Cymodocea rotundata, Halodule uninervis, Halophila ovalis, and Syringodium isoetifolium. A type of seagrass that is rarely found is Cymodocea serrulate which is only found in Loborai. The highest species density at Bodae station is Halodule unservices, and the lowest at Bodae station is Enhalus acoroides. The diversity index of seagrass species at the three stations is included in the low species diversity category. Seagrass species uniformity index is included in the medium community category. The dominance index of seagrass species at 3 stations is in the low dominance category. The highest coverage was Halodule uninervis with a value of 42.74% and the lowest was Enhalus acoroides with a value of 0.69%. The extent of seagrass cover at each of the Bodae, Laborai, and Keliha locations is 69.09%, 62%, and 66%, respectively. The highest Importance Value Index was found in Halodule uniservis, namely 138.00%, 30.55%, 96.80%, and the lowest was in Cymodocea serrulate. Overall the health condition of the seagrass beds at the observation location is included in the healthy category.